Cascaded H-Bridge Multilevel Inverter with Unequal DC Sources - Modagi, Shankar. A.; Raju, H. V. Govinda (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
Now a days the development of enthusiasm for multilevel inverters has been expanding on the grounds that there are huge uses of there in FACTS and modern drives and so on., Although there are numerous topologies of multilevel inverters in literature, mainstream among them are cascaded Hbridge. All in all the control techniques for these cascaded inverters are planned a suspicion of having all dc source voltages same for all H-bridges. This paper examines the capacities of cascaded multilevel inverter to create more output voltage levels with same number of H-bridges, yet with various input voltage proportions. The ideal nature of input dc voltage sources is shown as advantage in this paper. Total Harmonic Distortion (THD) is analyzed by simulation in MATLAB / Simulink.